in Traditional Persian Medicine - Majid Nimrouzi PhDc; Ali Mahbodi PhD; Amir-Mohammad Jaladat PhDc; Abbas Sadeghfard MS; Mohammad M. Zarshenas PhD (SAGE Publishing, 2014)
Traditional Persian medicine is based on humoral medical concepts. In the case of abundant blood in the body, tabi'at (body nature) deals with this imbalance by elimination of the morbid substances via some controlling mechanisms. If tabi'at could not react properly, the physician should prescribe an intervention to let the extra blood out. This can be done through phlebotomy, wet cupping, and the use of leech or scarification of the ears. Cupping with scarification may eliminate the morbid substance through the scarified skin, and cupping without scarification evacuates the morbid materials from the compromised organs. Wet cupping in health state is meant to be applied for preventing the blood humor dominance in susceptible individuals. In disease condition, wet cupping is defined as a treatment in which the patients confront the abundance of blood. Wet cupping may have harmful complications in extremely thin or obese patients. Wet cupping should be postponed in patients compromised by diseases especially in the thick phlegm abundance. In Asia, Iranian people, because of religious beliefs, are very interested in cupping therapy. Many unsupervised cupping procedures are performed in Iran, whereas benefits and risks of these procedures are undetermined by providers and clients. In this study, the most important indications and contraindications of wet cupping have been reviewed based on the traditional Persian medicine resources.